2013
DOI: 10.4269/ajtmh.12-0583
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Human Blood in Triatoma dimidiata Captured Inside Dwellings in a Rural Community in the Yucatan Peninsula, Mexico, but Low Antibody Seroprevalence and Electrocardiographic Findings Compatible with Chagas Disease in Humans

Abstract: Abstract. We studied a small rural community of 411 inhabitants localized in the state of Campeche in the Yucatan Peninsula, Mexico. In 44 collected triatomines captured inside the houses, human feeding source was revealed in 23 of 44 (52%) samples, and chicken feeding source was revealed in 16 of 44 (36%) samples. In a set of 29 triatomines, mouse was the feeding source in 13 (44%) samples, and dog was the feeding source in 7 (24%) samples. Infection index with Trypanosoma cruzi in collected triatomines was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In a recently published paper it was reported that T. dimidiata in this region is preferentially infected with T. cruzi I (Monteon et al 2013). In this present work we extended our findings using multiple sequence analysis of mini-exon intergenic region of a set of five T. cruzi isolates from Yucatan peninsula and two additional geographically nonrelated Mexican strains.…”
Section: Introductionsupporting
confidence: 81%
“…In a recently published paper it was reported that T. dimidiata in this region is preferentially infected with T. cruzi I (Monteon et al 2013). In this present work we extended our findings using multiple sequence analysis of mini-exon intergenic region of a set of five T. cruzi isolates from Yucatan peninsula and two additional geographically nonrelated Mexican strains.…”
Section: Introductionsupporting
confidence: 81%
“…It is interesting to note that a recent article from the Yucatan reports a high incidence of Triatoma dimidiata , an important vector of Chagas disease in Central America, feeding on humans but a very low incidence of Chagas disease. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Between 17% and 33% of domestic and periurbanmammal species have been reported infected with T. cruzi in the YP (Zavala-Velazquez et al,1996;Ruiz-Piña and Cruz-Reyes, 2002;Jimenez-Coello et al, 2008;Rebollar-Tellez et al, 2009). Livestock and pets also have similar infection prevalence between 5% and 34% (Hernandez et al, 2010;JimenezCoello et al, 2010;2012a;2012b;Monteón et al, 2013;Carrillo-Peraza et al, 2014). The human population in the YP has a heterogeneousT.…”
Section: Introductionmentioning
confidence: 86%
“…Several studies have now reported extension of natural distributions and sympatry for all three haplogroups, h1 and h2 have both been found in the Yucatan Peninsula (YP) (Bargues et al, 2008;Dorn et al, 2009;Gómez-Palacios and Triana 2014), and h2 and h3 in northern Chiapas (Pech-May, personal communication). Triatoma dimidiata infests between 8% and 61% of houses in the YP, with colonization indices between 5% and 25% (Guzman-Marin et al, 1990;Dumonteil et al, 2002;Hernández et al, 2010;Monteón et al, 2013). Many natural hosts of the dimidiata complex from modified habitats (i.e.…”
Section: Introductionmentioning
confidence: 97%